Effect of Bio-Dynamic Manure on Growth Yield and Quality of Pigeon Pea Under Climatic Condition of Bindh Region - Dr. PK Singh; Dr. Rashmi Singh; KVK Sonbhadra (Central Asian Journal of Theoretical and Applied Science, 2022)
Biodynamic agriculture was born when Dr Rudolf Steiner gave eight lectures about a new method of agriculture to a large group of farmers in Germany, in 1924. Rudolf Steiner was an Austrian philosopher and scientist who's thought was very much influenced by oriental philosophy, especially Buddhism, Hinduism, and the Vedic scriptures. Out of this influence and his own studies was born Anthroposophy, or the wisdom (knowledge) of the human being:At the heart of Anthroposophy is the recognition that the human being (Manushya) is a spiritual being (Purusha). Biodynamic agriculture was Steiner's answer to the farmers' call for help during the beginning of chemical farming in Europe when they noticed the rapid degeneration of the soil, of the quality of the produce, and of seed viability. They had been noticing a general decrease in vitality. Steiner then presented a different way of looking at cultivation and the Earth in general, showing the inter-relationship and connections between all living things.He explained how modern science and therefore chemical agriculture was based on the study of dead things in laboratories, rather than on the observation of living nature and the complex relationships constantly changing therein. Among this web of life he also included the cosmos with its moving planets and stars, and he spoke of how in the past, farmers instinctively knew about the effects of this movement on the life of plants and also animals and human beings. As modern human beings, we must find this connection once more to understand how to work best with nature, but this time in a very conscious, measurable way.Today there are many people around the globe who concentrate on understanding and recording the effects of the cosmos on our planet Earth, including Maria Thun in Germany who publishes a planting calendar for gardeners and farmers to use. Rudolf Steiner introduced a few preparations based on homeopathic medicine to enhance the beneficial cosmic influences on plants and the soil, and encouraged people to experiment and find new ones as well.